Mitochondrial Dynamics: An Attractive Therapeutic Target for Ischemia-Reperfusion Injury in the Heart - Rosdah, Elisha Rosalyn; Zulissetiana, Eka Febri; Rosdah, Ayeshah Augusta (Cell and BioPharmaceutical Institute, 2024)
Myocardial infarction is one of the leading causes of death worldwide. Current treatments do not compensate for the loss of cardiomyocytes, thus progression to heart failure is often inevitable. In myocardial infarction, the occlusion of coronary arteries and sudden restoration of blood flow give rise to ischemia-reperfusion injury, which leads to cardiomyocyte death. Mitochondria are not only involved in the bioenergetic aspect of the heart but also play a pivotal role in cell death during ischemia-reperfusion injury. Their morphology dynamically changes via fusion and fission in a balanced manner to maintain cellular health. However, ischemia-reperfusion injury triggers excessive mitochondrial fission, which is pathological to the myocardium. This review article discusses the association between myocardial ischemia-reperfusion injury and mitochondrial dynamics, serving as a rationale for a novel therapeutic strategy for myocardial infarction. Strategic modulation of mitochondrial dynamics under this pathological setting has been shown to be effective for cardioprotection. Increasing mitochondrial fusion or reducing excessive mitochondrial fission in the myocardial tissue could prevent cardiomyocyte death, thereby reducing infarct size. Proof-of-concept studies have utilized small molecules and peptides to implement this strategy into in vivo myocardial ischemia-reperfusion injury models. However, there remains a need to address the issues of specificity, bioavailability, and potency of these pharmacological agents before future application in cardiovascular therapeutics. Nevertheless, there has been growing interest in this therapeutic strategy in recent years, rendering it an attractive approach for ischemia-reperfusion injury in the heart.Keywords: mitochondria, heart, ischemia-reperfusion, cardioprotection